Indication for mild therapeutic hypothermia based on an initial Glasgow Coma Scale motor score. Issue 1 (December 2015) - Hifumi, Toru; Kawakita, Kenya; Okazaki, Tomoya; Egawa, Satoshi; Kondo, Yutaka; Natsukawa, Tomoaki; Sawano, Hirotaka
Abstract Although neurological evaluation using the Glasgow Coma Scale motor score is mandatory for post-cardiac arrest patients, further study is required to determine if this score can be used as an indicator for mild therapeutic hypothermia. Although the current study conducted by Natsukawa et al. presents interesting data, there are some critical issues regarding study design, selection bias, and interpretation of study results that should be pointed out.